Penerapan Metode Tutor Sebaya dengan Model Pendampingan untuk Meningkatkan Perolehan NEM 10 Besar Kota Mataram - Nanik Yuliani (Universitas Pendidikan Mandalika, 2022)
The purpose of this study is to apply the peer tutoring method with a mentoring model to increase the acquisition of the Top 10 NEM in Mataram City. This research method uses a descriptive method with a best practice approach. The subjects of this study were students of SMPN 2 Mataram. The instrument used is observation and material assistance. The data obtained from this study were analyzed descriptively. The results of this study indicate that the application of the peer tutoring method with the mentoring model is proven to be able to improve the results of the National Examination, it is known based on the results of the National Examination with the acquisition of the top 10 cities of Mataram. With the success of this research, teachers can use the peer tutoring method as an alternative to solving problems related to the acquisition of students' UN scores that have not been optimal.